Implementation of a Dyad-Based Intervention to Improve Antiretroviral Therapy Adherence Among HIV-Positive People Who Inject Drugs in Kazakhstan: A Randomized Trial. (March 2023) - Davis, Alissa; Mergenova, Gaukhar; Landers, Sara E.; Sun, Yihang; Rozental, Elena; Gulyaev, Valera; Gulyaev, Pavel; Nurkatova, Mira; Terlikbayeva, Assel; Primbetova, Sholpan; Altice, Frederick L.; Remien, Robert H.
Purpose: HIV-positive people who inject drugs (PWID) in Kazakhstan face many challenges to antiretroviral therapy (ART) adherence. Interventions that leverage social support from an intimate partner, family member, or friend may be effective in improving ART adherence among this population. The purpose of this paper is to describe the implementation process of a dyad-based intervention among HIV-positive PWID and their treatment support partners.Method: Sixty-six HIV-positive PWID and 66 of their treatment support partners will be enrolled in this pilot randomized controlled trial in Almaty, Kazakhstan, and randomized as dyads to receive an adapted version of the SMART Couples intervention or standard of care.Results: Several implementation strategies were used to facilitate intervention delivery, including remote delivery, training of staff, supervision, technical assistance, quality assurance, and collection of assessments through diverse sources.Discussion: This trial responds to a need for dyad-based ART adherence interventions adapted specifically for HIV-positive PWID.